Pengaruh Screen Layer Breakwater Terhadap Tinggi Run UP Gelombang pada Revetmen - Budiman, Budiman (INTEK: Jurnal Penelitian, 2018)
Erosion that occurs in revetment by waves and currents is a serious problem along coastal and inland shore ï›1ï. The aims of the study are to obtain influential parameter, to reduce the height of run up in the revetmet and get a non dimensional parameter of the relationship between the wave height and the wave run up on the revetment. The research is an experimental research with 2D physical model simulation, conducted in the laboratory of with some configurations of screen layer breakwater configuration models made from textile fabric with density and number of layer of different models. The model scale was 1:10 with three variations for models ((M1SL, M2SL, and M3SL) with variations of wave length and wave height, on some level of depth: 20, 15, and 10 cm. The results of the research indicated that the parameters found in this study are wave period (T), wave height (H), water depth (d), screen density (), the number of layers (N) and the distanceof the screen (Xm). The run up tend to decrease as the screen density value has smaller number of layers (N) and the distanceof the screen (Xm). In general, the study indicated that the stake of the screen layer can reduce the height of the run up in the revetment structure . The slope tan300 was 33% and produces non regression equation that shows the relationship between the dimensionless parameterwith run up (Ru/H), obtained Ru/H =, where= (); a and b respectively 2.9935 and 0.1293.